2022
DOI: 10.1002/ptr.7575
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin improves high‐fat diet‐induced obesity by modulating gut microbiota and metabolites in C57BL/6J mice

Abstract: High-fat diet-induced obesity is characterized by low-grade inflammation, which has been linked to gut microbiota dysbiosis. We hypothesized that quercetin supplementation would alter gut microbiota and reduce inflammation in obese mice. Male C57BL/6J mice, 4 weeks of age, were divided into 3 groups, including a low-fat diet group, a high-fat diet (HFD) group, and a high-fat diet plus quercetin (HFD+Q) group.The mice in HFD+Q group were given 50 mg per kg BW quercetin by gavage for 20 weeks. The body weight, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…Quercetin was more abundant in CF than in UF and it was reported that it could improve gut microbial disorders and affect the production of gut microbial metabolites related to oxidative stress. 71 The abundance of Bacteroides in the CF group was lower than that in the UF group, and the abundance of Roseburia in the CF group was higher than that in the UF group, likely owing to the increased naringin in CF. 72,73 Furthermore, proanthocyanin B1 increased after fermentation, and proanthocyanins can protect gut microbiota from perturbation.…”
Section: Papermentioning
confidence: 82%
“…Quercetin was more abundant in CF than in UF and it was reported that it could improve gut microbial disorders and affect the production of gut microbial metabolites related to oxidative stress. 71 The abundance of Bacteroides in the CF group was lower than that in the UF group, and the abundance of Roseburia in the CF group was higher than that in the UF group, likely owing to the increased naringin in CF. 72,73 Furthermore, proanthocyanin B1 increased after fermentation, and proanthocyanins can protect gut microbiota from perturbation.…”
Section: Papermentioning
confidence: 82%
“…Its anti-obesity effect is due to the inhibition of adipogenesis by inhibiting the gene expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) 30 . Quercetin is reported to significantly alleviate high-fat-diet-induced obesity and influence the production of metabolites linked to obesity-related inflammation and oxidative stress by regulating gut microbiota and metabolites 31 . EGCG is a bioactive polyphenol with antioxidant and antiinflammatory effects 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vivo and in vitro studies have found that CAPE can inhibit the differentiation of mouse preadipocytes and prevent adipogenesis (30,31), and its specific mechanism will be discussed in the next chapter. In addition to phenolic acids, flavonoids, such as chrysin, galangin, apigenin and quercetin, exhibit excellent antiobesity effects through different mechanisms (32)(33)(34)(35).…”
Section: Poplar-type Propolismentioning
confidence: 99%